HISTOPATHOLOGICAL CHANGES IN THE GILLS OF CHANNA GACHUA, AN AIR BREATHING TELEOST AFTER SHORT TERM EXPOSURE OF HOSTATHION - JHA, JEEBU KUMAR; RANJANA; KUMAR , PANKAJ; A. P. MISHRA (The Bioscan, 2014)
Gills are the prime organs for gaseous exchange and perform several other physiological functions including osmoregulation and excretion. Harmful effects of several insecticide on the gill histomorphology are well known. In this paper the effects of a commonly used insecticides on the gills of C.gachua is demonstrated. Channa gachua, a freshwater teleost was exposed to a broad spectrum organophosphate insecticide hostathion for 24, 48, 72 and 96h at 0.25, 0.30, 0.35 and 0.40ppm. 96h LC50 value was determined. The histological sections of gills of snake headed air breathing teleost examined under light microscope showed severe structural alterations like mucus cells hyperplasia, buldging of taste buds, formation of interlamellar bridge and sub epithelial spaces in the primary and secondary gill lamellae.